Role of shear-wave and strain elastography to differentiate malignant vs benign subpleural lung lesions. Issue 1 (8th January 2021) - Boccatonda, Andrea; Susca, Valentina; Primomo, Gian Luca; Cocco, Giulio; Cinalli, Sebastiano; Di Resta, Velia; Martino, Laura; Mucilli, Felice; Marinari, Stefano; Cipollone, Francesco; Schiavone, Cosima
Abstract : Abstract: Elastosonography is a non-invasive diagnostic method to evaluate tissue stiffness. The aim of our study was to demonstrate the applicability and efficacy of elastosonography to differentiate benign vs malignant subpleural lung lesions compared to clinical, radiological and histological findings. We performed both strain and shear wave velocity (SWV) elastosonography on subpleural lung lesions. Moreover, we elaborated a composite score called "elasto index". Fourteen patients, 10 males and 4 females were recruited. On strain elastography, 9 lesions showed a hard pattern (type 3), 3 lesions showed an intermediate pattern (type 2), and 2 lesions a soft pattern (type 1). All lesions showed a mean SWV value of 4.46 ± 2.37 m/second. The mean SWV for malignant lesions (n = 6) was 5.92 ± 2.8 m/second. The mean SWV for benign lesions (n = 8) was 3.36 ± 1.20 m/second. SWV shows an area under the curve (AUC) of 0.792, and the Youden index shows a value of 3.6 m/second. The ROC curve elaborated for the diagnosis of malignancy by strain elastography showed an AUC of 0.688. ROC curve for the diagnosis of malignancy by elasto index demonstrated an AUC of 0.802. SWV values obtained by ARFI elastosonographic method are higher in malignant lung lesions (mean SWV: 5.92 m/second) than in benign ones (mean SWV: 3.36); a composite score (elasto index) is characterized by better statistical significance for the differentiation of the lesions.